Insights into the degradation of 2, 4-dichlorophenol in aqueous solution by α-MnO2 nanowire activated persulfate: catalytic performance and kinetic modeling. Issue 42 (11th April 2016) - Zhao, Yan; Zhao, Yongsheng; Zhou, Rui; Mao, Yan; Tang, Wen; Ren, Hejun
Abstract : α-MnO2 nanowires were synthesized through a hydrothermal method. Sulfate and hydroxyl radicals were produced in α-MnO2 -activated persulfate system to degrade 2, 4-dichlorophenol. Abstract : In this study, α-MnO2 nanowires were synthesized in a hydrothermal process. These nanowires efficiently activated persulfate (PS) for 2, 4-dichlorophenol (DCP) oxidation. The shape and structure of the material were characterized through X-ray diffraction, high-resolution transmission electron microscopy, and energy dispersive X-ray spectroscopy. Quenching tests and electron paramagnetic resonance were conducted, and the results revealed that both ˙OH and SO4 ˙ − were responsible for the degradation of 2, 4-DCP in the α-MnO2 -activated PS system. A novel kinetic model was established to describe the deterioration of the contaminant under the conditions described in this paper. Several key parameters are investigated in the evaluation process of the kinetic study, including catalyst dosage, PS concentration, pH, and temperature. The maximum removal efficiency of 2, 4-DCP was 90.2% at 20.0 mM PS, given 0.2 g L −1 α-MnO2 nanowires, and under a temperature of 30.0 °C. In addition, the α-MnO2 nanowires exhibited relatively stable catalytic activity after five instances of reuse. The aforementioned results indicate that α-MnO2 nanowires are promising catalysts for the activation of PS to degrade organic contaminants in wastewater.